(3eLehY aj GdcjejGAs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3hGYde Cf GdCcSjQ GdCYXe dg NhGU YLjHI hbO QCjfGgG hGeJMfGg ahLOfGgG UMjMI hefgG SQjY hefgG s
(3BNQgG (B:s
(3hbO YdeJ HeG hUaJg jG Hfi hLQJg aUM hde jHWd Ydjg efg TF Edi GdebYO HYO eQGJ cKjQI hai gPG GdMLQ CcKQ eeG hUaJ dc acf MGaXkG ddYdhe GdTQjaI GdLdjdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3hjTJed fSNI GdeNWhW Ydi (B5 (3ebGdGJ ai NhGU GdCcSjQ ef GdSGOSI MJi GdMGOjI YTQ Ke Jdj gPg GdebGdGJ QCi GdQGRi ai GdCcSjQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs